Performance evaluation and application of second-generation environmentally-friendly composite dust suppressant in dust control - Yong Xu; Yanghaoxu Wu; Ben Ma; Yingda Zhang; Yujie Fan; Xin Huang; Zihao Liu (Scientific Reports)
Abstract This study compares the performance of two generations of environmentally friendly composite dust suppressants, derived from plant straw, with two commercial suppressants, water, and dust-proof netting. The aim is to address construction-related dust pollution while minimizing environmental impact. Through wind erosion resistance tests under simulated high-wind conditions, the second-generation suppressant at 2 L/m2 concentration is found to decrease the soil mass loss, outperforming others in efficiency. Furthermore, a study on cabbage seed germination and growth under the influence of different solutions shows that the second-generation suppressant exhibits virtually no adverse effects, with results similar to water. In soil impact tests, the second-generation suppressant demonstrates the best solidification effect, with soil parameters meeting standards and outperforming both commercial suppressants and water. Overall, the second-generation environmentally friendly composite dust suppressant has shown favorable performance across all aspects, resulting in a suitable candidate for widespread use in dusty environments.